E-COMMERCE SEBAGAI PENDUKUNG PEMASARAN PERUSAHAAN - Melgiana Medah (Politeknik Pertanian Negeri Kupang, 2009)
E- commerce as a manufacturing marketing support. E-commerce very support in raise, development for manufacturing. E-commerce will give a proper to management in a labor to do of process. Between labor, e-commerce is very support marketing in manufacturing to get income, because it can change of service. A time ago the consumer came and bought at a manufacturing but now the consumer canon line every time, everywhere they can make a transaction.Consumer can see the all activities and product of manufacturing. E- commerce action as a support for give information and reference about product agricultural marketing, or industry manufacturing, especially advertisement on internet mediaKey word: Managemen, e-commerce, Marketing, Marketing Strategi